2015
DOI: 10.5005/jp-journals-10006-1353
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Selected Antenatal Exercises in Reduction of Labor Pain among Primigravid Women: Implication for Practice

Abstract: Purpose: Labor is a physiological event, but it is a painful event.The agony and stress a woman suffers are beyond description. Primigravid women must be prepared during the antenatal period itself for safe and natural childbirth. The purpose of this study was to determine the effect of antenatal exercise in pain management during labor. Materials and methods:A quasi-experimental study was conducted with 600 primigravid women. Education on antenatal exercises provided with the help of three-dimensional (3D) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Of these, nine were RCTs and one was a quasi-experimental study. Two studies were conducted in the USA [ 19 , 20 ], two in India [ 21 , 22 ], one in Taiwan [ 23 ], one in New Zealand [ 24 ], one in Australia [ 25 ], one in Brazil [ 26 ], one in Iran [ 17 , 18 ], and one in Sweden [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, nine were RCTs and one was a quasi-experimental study. Two studies were conducted in the USA [ 19 , 20 ], two in India [ 21 , 22 ], one in Taiwan [ 23 ], one in New Zealand [ 24 ], one in Australia [ 25 ], one in Brazil [ 26 ], one in Iran [ 17 , 18 ], and one in Sweden [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Participants received a guide with the exercises to be performed daily at home, consisting of pelvic floor muscle training (PFMT) including rapid (30 times) and sustained maximal contractions (20 times holding for 10 s), stretching exercises to reduce back pain and exercises to improve venous return in the lower limbs Information about breathing exercises for birth. Relaxation at home: Training of breathing techniques for contraction control during labour, Training of breathing techniques for contraction control during labour; progressive relaxation techniques; massage; mentalisation monthly from 18–24 weeks until 30 weeks’ gestation; fortnightly till 36 weeks; Duration 50 min 18–24 weeks’ gestation Duration of labour, Memory of labour pain (VAS), Mode of birth 1 st min and 5 th min Apgar score > 7, Birthweight > 2500 g Secondary outcome = 78 Secondary outcome = 71 Pan, 2019 [ 23 ] RCT 35 39 • Adaptation of MBCP by Nancy Bardack • Transformative experience of pregnancy, childbirth, and postpartum-related adjustments in self-awareness training • Listen to programme-related audio recordings at home six times a week for 30 min each Three-minute breathing space 8 weeks; Series of nine three-hour classes held once per week and one seven-hour day of silent-meditation practice After recruitment between 13 and 28 weeks’ gestation Childbirth self-efficacy (CBSEI) Prince, 2015 [ 22 ] Quasi-experimental 300 300 • Antenatal exercises by video training (animated and easily understandable) • Antenatal techniques included breathing exercises, relaxation exercises and pelvic floor muscle exercises • Information about pregnancy and labour, benefits of selected antenatal exercise, types of exercises, selected exercises during pregnancy and labour • Each primigravid women was given a record sheet to record the exercises performed at home with relevant instructions and a compact disk (CD) was provided for their practice NI 34 weeks up to birth; Once (45 min), practice at home (< 200 up to > = 400 h) NI Memory of labour pain (VAS) Timm, 1979 [ 20 ] RCT ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study proved that knowledge level of primigravid women in the experimental group showed significant improvement on selected antenatal exercises after video assisted teaching programme. Antenatal education program on selected antenatal exercises should be a routine activity and a service to be delivered by nurses and midwives in the antenatal, outpatient department and in the in labor unit [1][2][3][4][5].…”
mentioning
confidence: 99%